The Geological Structures Formed Influence the Process of Mineralization in the Beruang Kanan Area, Gunung Mas Regency, Central Kalimantan - Retno Anjarwati; Sutarto Sutarto; Dwi Fitri Yudiantoro; Arifudin Idrus (Jurnal Indonesia Sosial Teknologi, 2024)
The Schwaner Mountains stretch in the middle. Identification of geological structures that play a role in the formation of metallic mineral deposits is necessary for more efficient mining exploration and exploitation. The Right Bear is a mining site located on a remote hill in the central part of the island of Kalimantan. This study aims to determine the condition of geological structure and the influence of geological structure on the distribution of copper mineralization at the research site. In this study, surface data was collected in the form of lithological description data and data on the structure of bridles and veins in rocks. The equipment used is a geological compass, a geological hammer, GPS, a magnifier, and others. In general, the stratigraphy of the research area is divided into 3 rock units that can be seen on the geological map, in order from old to young, namely the lithology of the Sandstone Unit, the Dacitic Tuf Unit, the Andesite Unit, and the Quartz Sand Deposit Unit. The mineralization of the Right Bear area consists mainly of high Cu sulfide mineralization. It is related to copper mineralization. Associated mineralization is generally controlled by bridle and fault structures. Mineralization is hosted by volcanic and volcaniclastic rocks in the research area, especially in the middle and southeast of the research area. The geometry of a vein with a width of > 1 cm is called a vein, if it is < 1 cm wide it is called a vein and if it is < 1 mm it is called a vein cord. These veins generally have the direction NNE SSW, NE-SW, NW-SE and WNW-ESE.